Pertumbuhan Kecambah Aren (Arenga pinnata (Wurmb.) Merr) dari Pohon Induk Berbeda Ketinggian dengan Pemberian Pupuk Organik - Muhammad Salim Saleh; , nFathurrahman (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
The aim of this research was to study the growth of sugar palm seedling from different altitudes of mother plant, growing in different organic media. The experiment was conducted at Seed Technology Laboratory and Academic Garden of Agronomy Department, Faculty of Agriculture, Tadulako University, from February to July 2008. The experimental design was factorial randomized block design with two factors. The first factor was seed from different altitudes of mother plant sources, i.e, : from Parigi (<500 m asl), from Palolo (500-1,000 m asl), and from Napu (>1,000 m asl). The second factor was types of organic fertilizers added on soil taken from sugar palm land. The organic fertilizer treatments were without fertilizer, manure, compost of rice husk, and sugar palm residue. Each experimental unit was comprised of 25 seeds with three replications. The results showed that seeds from Parigi grown in media with compost of rice husk gave a better growth than other treatments. Germination percentage at this treatment was 88.01% and dry weight of seedlings was 0.41 g in average, eligible to be transferred to main nursery.